Enhancing nutritional and functional properties of gluten-free Riceberry rice pasta supplemented with cricket powder using D-optimal mixture design - Musika, Jirayu; Kapcum, Chutikarn; Itthivadhanapong, Pimchada; Musika, Thanawan; Hanmontree, Pannapa; Piayura, Sumeth (Frontiers in Sustainable Food Systems, 2024)
The study aimed to develop gluten-free Riceberry rice pasta supplemented with cricket powder using a twin-screw extruder, contributing valuable knowledge to increasing the nutritional value of pasta through sustainable practices, nutritional enhancement, and novel ingredients. A D-optimal mixture design, an effective statistical tool for optimizing formulation, was used to determine the optimal proportions of Riceberry rice flour (RF, 75-90%), cricket powder (CP, 5-20%), and xanthan gum (XG, 1-5%). The results showed that all predictive models were statistically significant with satisfactory coefficients of determination (R² ≥ 0.75), statistically significant (p ≤ 0.05), and exhibited a nonsignificant lack of fit. The contour plot demonstrated that pasta with high RF, XG, and low CP contents had the lowest L* and highest a* values. The incorporation of XG increased firmness, while an increase in CP led to higher protein and fat contents in the pasta. A decrease in RF resulted in reduced total phenolic content (TPC), anthocyanin content (ATC), and 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) scavenging activity (AOA). The sensory evaluation scores of the pasta, in terms of the texture attribute and overall acceptance, decreased as the proportion of XG increased. The optimization analysis showed that the highest desirability was achieved with RF, CP, and XG at 84.10, 14.45, and 1.45%, respectively. The optimally desirable product had the following properties: L* at 22.60, a* at 4.80, b* at 4.78, firmness at 3.41 N, protein content at 12.57%, fat content at 4.68%, TPC at 360.13 mg GAE/100 g dw, ATC at 476.24 mg C3G/100 g dw, AOA at 25.10 mg TE/100 g dw, texture rating at 7.40, and overall acceptance rating at 7.01. This study highlights the potential of cricket powder as a protein source in gluten-free Riceberry rice pasta. It offers insights into the effects of ingredients on pasta quality and facilitates the development of nutritious and appealing gluten-free pasta.